Fluorescent Organic π‐Radicals Stabilized with Boron: Featuring a SOMO–LUMO Electronic Transition. (21st April 2022) - Ito, Masato; Shirai, Shusuke; Xie, Yongfa; Kushida, Tomokatsu; Ando, Naoki; Soutome, Hiroki; Fujimoto, Kazuhiro J.; Yanai, Takeshi; Tabata, Kenichi; Miyata, Yasuo; Kita, Hiroshi; Yamaguchi, Shigehiro
Abstract: We report on the fluorescence properties of a new class of emissive and stable π‐radicals that contain a boron atom at a position distant from the radical center. A fully planarized derivative exhibited an intense red fluorescence with high fluorescence quantum yields ( Φ F >0.67) even in polar solvents. To elucidate the origin of this phenomenon, we synthesized another boron‐stabilized radical that contains a bulky aryl group on the boron atom. A comparison of these derivatives, as well as with conventional donor–π–acceptor (D–π–A)‐type emissive π‐radicals, unveiled several characteristic features in their photophysical properties. A theoretical analysis revealed that the SOMO–LUMO electronic transition generates an emissive D1 state. Unlike conventional D–π–A‐type π‐radicals, this state does not undergo significant structural relaxation. The boron‐stabilized π‐radicals demonstrated promising potential for organic light‐emitting diodes as an emitting material. Abstract : A design strategy of emissive and stable π‐radicals is established based on incorporation of a boron atom at a position distant from the radical center. SOMO–LUMO electronic transition in the boron‐containing π‐radicals gives rise to intense red fluorescence, irrespective of solvent polarity, different from donor‐π‐acceptor‐type emissive π‐radicals.